Comparison of Gd-Bz-TTDA, Gd-EOB-DTPA, and Gd-BOPTA for dynamic MR imaging of the liver in rat models - Twei-Shiun Jaw; Shih-Hsien Chen; Yun-Ming Wang; Jui-Sheng Hsu; Yu-Ting Kuo; Yen-Yu Chiu; Kun-Bow Tsai; Tsyh-Jyi Hsieh; Gin-Chung Liu (Kaohsiung Journal of Medical Sciences, 2012)
To evaluate the competitive potential of a new lipophilic paramagnetic complex, Gd-Bz-TTDA [4-benzyl-3,6,10-tri (carboxymethyl)-3,6,10-triazado-decanedioic acid] compared with two other commercially available MR hepatobiliary contrast agents, gadobenate dimeglumine (Gd-BOPTA) and gadoxetic acid (Gd-EOB-DTPA), dynamic MR imaging studies were performed on normal and hepatocellular carcinoma (HCC) rat models using a 1.5-Tesla MR scanner. The results indicate that normal rats that were injected with 0.1 mmol/kg Gd-Bz-TTDA showed significantly more intense and persistent liver enhancement than those that were injected with the same dose of Gd-EOB-DTPA or Gd-BOPTA. All of these agents showed similar enhancement patterns in the implanted HCC. The liver-lesion contrast-to-noise ratios were higher and more persistent in rats that were injected with Gd-Bz-TTDA. These results indicate that Gd-Bz-TTDA is comparable with the commercially available hepatobiliary agents, Gd-EOB-DTPA and Gd-BOPTA, and can result in more intense and prolonged liver enhancement while still providing better liver-lesion discrimination. These results warrant further large-scale studies.